Lattice distortion of quantum cryocrystals under pressure: Cryocrystals - Tretyak, S.M.; Antsygina, T.N.; Freiman, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The hcp lattice distortion parameter d, the deviation of c/a ratio from the ideal hcp value √8̅/̅3̅ , have been calculated for solid He under pressure taking into account two- and three-body interatomic forces. The resulting lattice distortion parameter is small and negative, that is the lattice is slightly flattened compared with the ideal hcp lattice. It monotonically increases in absolute value with pressure and reaches 10–3 for molar volume of 2.5 cm3/mol. Such small distrotions are most likely outside of possibilities of x-ray or neutron experiments but can be detected by optical methods based on measurements of the birefringence. The data on d can be used as a probe of the many-body forces.